Basic Statistical Concepts On Neutrosophic Soft Sets, Neutrosophic Sets and Systems - Siva Naga Malleswari V; Amarendra Babu V; Bhagya Lakshmi K (Neutrosophic Sets and Systems)
This study explores the basic statistical measures—mean, standard deviation, covariance, and correlation—within the framework of neutrosophic soft sets. Neutrosophic soft sets provide a powerful mathematical model for handling uncertainty, indeterminacy, and inconsistency in real-world data analysis. The study defines and formulates these statistical concepts under neutrosophic soft environments, incorporating true, indeterminate, and false memberships. A systematic approach to computing the neutrosophic soft mean and standard deviation is presented to measure central tendency and data dispersion. Furthermore, neutrosophic soft covariance and correlation are examined to analyze relationships between uncertain datasets. Practical applications in decision-making, medical diagnostics, and financial analysis demonstrate the effectiveness of these statistical tools. This research enhances statistical methodologies for uncertain data, offering a robust analytical foundation for fields requiring flexible and reliable data interpretation.